Enhancement of Cadmium and Zinc Flame Spectrometric Signals by Using APDTC-nButylamine-MIBK Extractants - Tee, Tan Wee; Keong, Wong See (1990)
Ammonium pyrrolidine-dithiocarbamate (APDTC) and methyl-isobutyl-ketone (MIBK) extractant were jound to be considerably improved by the addition of nbutylamine especially for the chemical analysis of Cd(II) and Zn(II) ions. Solvent extraction oj the bivalent metal ions is a function of pH and the concentration of APDTC and nbutylamine. Cd(II) and Zn(II) ions exhibit considerable flame spectrometric signal enhancement for pH ranges from 7 to 12 and 2 to 12 respectively when APDTC-nbutylamine-MIBK was used as the extractant in place oj APDTC-MIBK. The signal enhancement observed may be interpreted in terms of the formation of synergistic amine adduct and/or mixed solvent effect.